TEXT PRODUCTION AS A STRATEGY FOR DEVELOPING LITERACY IN THE EARLY YEARS OF ELEMENTARY SCHOOL - Maria da Silva Siqueira, Antonia; Siqueira dos Santos, José; Andréia Coutinho Orosco Plaça Pires, Luciana (Revista Gênero e Interdisciplinaridade, 2026)
Literacy in the early years of Elementary Education must go beyond the mechanical mastery of the writing system, promoting practices that encourage the social use of language, as recommended by the Brazilian National Common Core Curriculum (BNCC). In this context, text production is a fundamental pedagogical strategy for the development of authorship and students’ linguistic competencies. This article aims to report a pedagogical experience developed in the early years of Elementary Education, focused on strengthening the literacy process through systematic text production activities. The proposal involved stages of reading, planning, writing, rewriting, and sharing texts, and was grounded in teacher mediation and in the work with textual genres appropriate to the students’ age group. The results showed advances in textual organization, vocabulary expansion, the use of cohesive devices, and students’ engagement with writing. It is concluded that text production, when developed in an intentional and contextualized manner, contributes significantly to the strengthening of literacy and to the development of autonomy and authorship in the early years of Elementary Education.